Examination of Hausa Terms and Concepts Used over Electronic Media in the Non-Speaking Hausa Area - Usman Ahmadu, Mohammed (Glottodidactica, 2005)
Specifically the study analyses the use of Hausa in three different areas i.e. a) the eastern Hausa dialect area where we sample Kaduna and Kano States b) the western Hausa dialect area where we sampled Sokoto and Katsina States and c) the non-Hausa speaking area where we sampled Adamawa and Plateau States all in Nigeria. Never the less for the sake of comparation we have considered some foreign electronic media that broadcast programmes in Hausa. Among these electronic media we distinguished between the African electronic media whereby we sampled Niger and Cameroon republics, which are Francophone neigboring Nigeria and the foreign electronic media whereby we sampled BBC-Hausa service and the VOA-Hausa service. Through various instruments of research, the study comes up with various performances of the Hausa Broadcasters in terms of IOVs, IOAs, IOCs, and IOIs. The study identifies that there are various degrees of variations among Hausa Broadcasters in the use of terms and concepts in the electronic media in all the areas. These variations are observed at different levels i.e. among Hausa Broadcasters in the same electronic media within the same dialect area and across electronic media. These variations occasion various degrees of performances among Hausa Broadcasters in terms of IOAs. The study further identifies various degrees of performances in terms of IOCs, which result in various degrees of performances in terms of IOIs. The performances of the Hausa Broadcasters result in confusions and breakdown of communication as reported by Hausa listeners. These variations and inconsistencies in the use of Hausa terms and concepts over the electronic media are tied up to various factors. The lack of a language monitoring body saddled with the responsibility of supervising Hausa language development in the media may be the cause of such discrepancies in the use of terms of concepts over all the electronic media that broadcast and feature programmes in Hausa within Nigeria as well as outside.